Diffractive and refractive lenses for hard x-rays with ultra-high efficiencies - Nöhammer, Bernd (My University, 2004)
Focusing of x-rays is an essential pre-requisite for many synchrotron based measurement techniques. In this work, multi-level silicon zone plates and planar refractive lenses made from diamond and silicon have been developed, aiming for focusing applications in the hard x-ray range, i.e. for photon energies between 10 and 50 keV. The first part of the work deals with diffractive x-ray lenses (zone plates) that utilize a multi-level profile for the diffracting structures in order to obtain high diffraction efficiencies. Theoretical calculations are presented, yielding the optimal design of a multilevel profile with respect to diffraction efficiency for the general case of absorbing grating materials. A micro-fabrication process is described, enabling the fabrication of silicon zone plates with a four-level profile of high quality for grating periods down to 800 nm and a grating structure height of 1.5 µm. For good efficiencies in the hard x-ray range significantly larger grating heights of about 5-50 µm are required. This was achieved using linear zone plates with line grating structures by tilting them with respect to the x-ray beam. The tilting allowed a tuning and a strong increase of the effective grating structure height. In consequence unprecedented diffraction efficiencies of 65 % in the energy range between 10 and 17 keV could be obtained. In order to achieve 2-dimensional focusing, two crossed linear zone plates in series were used. A focal spot size and a resolution of about 2 µm were found for the resulting micro-focusing device. Outstanding features of the device are its high total focusing efficiency (above 30%) and the extremely small divergence of 2.4×10-4 rad of the focused beam. Linear multilevel zone plates are therefore especially suited for focusing applications, which require large efficiency and small beam divergence rather than a small spot size and high resolution. The second part of this work deals with planar refractive lenses made from diamond and silicon. Both types of lenses were fabricated in a similar way using e-beam lithography and reactive ion etching. For both lenses the resolution is mainly determined by deviations from the ideal lens profile, which originate from the fabrication process. Theoretical considerations show that for a given fabrication process the obtainable resolution is directly proportional to the size of the lens aperture. For the comparatively large lens apertures realized within this work (100-600 µm) a resolution of the order of a few microns was achieved for both types of lenses. The potential applications of these planar refractive lenses depend on the lens material used. Silicon refractive lenses have the advantage that sophisticated methods for the structuring of silicon are available, but the disadvantage that x-ray absorption within silicon is comparatively large. Nevertheless, it was possible to reach good efficiencies of about 20-30% for large photon energies between 35-50 keV. As a consequence silicon lenses are valuable for micro-focusing applications in this x-ray range, where only very few types of lenses are available. Although much more difficult to structure than silicon, diamond has the advantage over silicon that it shows very low x-ray absorption. Therefore high efficiencies up to 80 %, even at comparatively low x-ray energies of 17.5 keV, could be reached with diamond lenses. In addition diamond has unique material properties such as a high thermal conductivity and high stability, which is of particular interest for applications in future X-ray free electron lasers (X-FEL). Such X-FELs are predicted to yield x-ray beams with peak intensities several orders of magnitude beyond those of present x-ray sources, and diamond refractive lenses are one of the few candidates for optical components, which are likely to withstand such a beam
Thèse de doctorat : Université de Neuchâtel : 2004 ; 1748